The Implementation of al-Mâ’ûn’s Theology in the Philanthropy of Muhammadiyah Citizens in Malaysia - Fahrudin Mukhlis (Universitas Darussalam Gontor, 2022)
The aim of this research is to describe the implementation of social solidarity from ‎the theological understanding of surah al-Mâ’ûn by the residents of ‎Muhammadiyah in Malaysia during the covid-19 pandemic. This research model is ‎a case study on the generosity behaviour of migrant workers or better known as the ‎Indonesian Migrant Workers (TKI) Muhammadiyah in Malaysia. This research ‎method uses a qualitative approach. The data collection technique is done by online ‎observation, interviews and documentation. This study applies an interactive ‎analysis through data collection, data reduction, presentation and conclusion ‎drawing. The purpose of this study is to determine the form of social activities ‎carried out by Muhammadiyah citizens in Malaysia who on the other hand are ‎migrant workers in response to the global covid-19 pandemic. The results of this ‎study can be concluded that the implementation of the value of social solidarity in ‎the Muhammadiyah community in Malaysia, especially for migrant workers, shows ‎that citizen philanthropy indirectly creates a cooperative activity, an activity of ‎mutual help and willingness to sacrifice for others. It is clear how some of ‎the residents participate in an unconditional way in trying to help other residents ‎who do not have basic needs due to the strict social distancing run by the ‎Malaysian Royal Government.